Microplastics accumulation in pacific oysters from Danang bay, Vietnam - Manh, Do Van; Thom, Dang Thi; Thao, Le Xuan Thanh; Thanh, Nguyen Duy; Manh, Duong Tuan; Viet, Pham Hung (Vietnam Journal of Science and Technology, 2022)
Microplastics (MPs) accumulation in marine environment has become the global concern in recent years. MPs in oysters were considered as potential pollution in the cultured farms in the coastal areas. This research identified MPs in pacific oysters Crassostrea gigas which are cultured in DaNang bay, Vietnam. The obtained results showed that the average MPs concentration in oyster about 2.36 ±2.14 items/g (wet weight) and 33.25 ±25.93 items/ individual.  The most abundant MPs size were in the range of 0-50µm (43.98%), followed by the range of 50-100 µm (37.59%) and the most common shape was fragments 79.32%, followed by fibers 20.30%. Chemical composition of MPs polymer types was detected by μ-FT-IR using Nicolet iN10 MX Infrared Imaging Microscope. The major polymer types of MPs were Nylon (28.57%), followed by Rayon (23.31%), Phenol resin (PFs 8.65%). The results indicated that MPs occurrence in pacific oyster from DaNang bay is an urgent environmental issue in order to implement for monitoring and improving MPs management in bivalves of Vietnam.